Game-Based Learning and Children’s Digital Literacy to Support Pervasive Learning: A Systematic Reviews - Fadhli, Muhibuddin; Kuswandi, Dedi; Utami, Prihma Sinta; Sartika, Septi Budi; Mohamad Hardyman bin Barawi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
In this study, we investigate the impact of game-based learning on children's digital literacy in processing and acquiring information, focusing on the generation of digital natives who excel in responding to multimedia information. Utilizing data mining and the PRISMA Protocol, we conducted a systematic review based on the keywords 'Game-based learning on children’s digital literacy.' Data from the years 2017 to 2019, extracted from Sagepub and Emerald databases, reveal strong empirical support for the enhancement of children's digital literacy, particularly through game-based learning interventions, as evidenced by a significant effect size of 0.66. This translates to children becoming better at deciphering visual cues, understanding audio narratives, and critically evaluating the information presented in a variety of multimedia formats. Furthermore, game-based learning fosters critical thinking and problem-solving skills, keeping children engaged and motivated to learn in this dynamic digital landscape.